PRACTICE MICROSOFT OFFICE AND COMPUTER SECURITY FOR ADMINISTRATORS AND EMPLOYEE OF SENNA_MUA_GALLERY - hilda yunita; Hamdan Syukri (Universitas Nahdlatul Ulama Lampung, 2021)
Senna_Mua_Gallery was a Wedding Organizer (WO) that located at Untung Suropati Street, Bandar Lampung. In daily activity, WO`ve used computer, but knowledge of employees about computer especially Microsoft Office app, it was Microsoft Excel and Microsoft Power Point and Computer Security that slow down activity who used used computer hardware. Training for Senna_Mua_Gallery employees held as one of team concern. Community dedication held for giving training Microsoft Office and computer security especially about Microsoft Word, Microsoft Excel and Microsoft Power Point for ADMINISTRATORS and employees ability in number processing well and report presentation. This held as time plan, Administrators and employees have been applied computer programs what is needed.